Ferroelectric and photovoltaic properties of (Ba, Ca)(Ti, Sn, Zr)O3 perovskite ceramics. Issue 16 (15th August 2021) - Pan, Wen-Yuan; Tang, Yu-Cheng; Yin, Yang; Song, Ai-Zhen; Yu, Jing-Ru; Ye, Sheng; Zhang, Bo-Ping; Li, Jing-Feng
Abstract: Ferroelectric perovskite oxides exhibit the bulk photovoltaic effect, which enables an above-bandgap photovoltage, controllable photocurrent response, and higher efficiencies. Herein, the phase structure, ferroelectric, dielectric, light absorption, and photovoltaic properties in (Ba0.95 Ca0.05 )(Ti0.92 Sn0.08- x Zr x )O3 (BCTSZ x ) ceramics were investigated. All BCTSZ x samples had good ferroelectric properties along with a narrow band gap ( E g = 2.53–2.60 eV). A large photovoltaic response under AM 1.5 G simulated sunlight was observed in the poled BCTSZ0.06 ceramics, in which the maximum short-circuit current ( J SC = 3.66 nA cm −2 ) as well as the highest transient current ( J TC = 32.56 nA cm −2 ) and photocurrent ( J PC = 12.63 nA cm −2 ) were obtained in 500 μm-thick sample negatively poled at 30 kV cm −1 . Our results deepen an understanding of the ferroelectric photovoltaic mechanism of perovskite materials and provide a new material for photovoltaic and multifunctional applications.